World Family Portrait: Expresiones paisajísticas de la frontera Guatemala-México en la zona del Soconusco; Un alfabeto, dos universos. Issue 2 (1st June 2021) - Cervantes Salas, Mauricio Pablo; Harlan, Harlan; Maganda, Carmen
Abstract : In this issue Regions & Cohesion is proud to present a selection of four photographs submitted by Mauricio Salas Cervantes and taken by Felipe Morales Leal that describe a research visit within a multidisciplinary and multinational project in the transboundary Guatemala–Mexico region with a perspective of a landscape analysis. These pictures taken in the Suchiate river in Soconusco region show the complexity and plurality of one of the most transited crossing points between Mexico and Guatemala. We also publish two photographs by our editors Carmen Maganda and Harlan Koff that illustrate their research visit to the Costa Chica Guerrero, Mexico. These photos juxtapose the co-existence of two worlds in this region: one local and one global.